Prevalence, risk factors, and management of uncontrolled hypertension among patients with diabetes: A hospital-based cross-sectional study - Almalki, Ziyad S. (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2020)
• Uncontrolled hypertension is highly prevalent in diabetic patients. • Hypertension is uncontrolled mainly in older, male, and obese patients. • Preventive strategies for screening, treatment, and monitoring of BP are required for the diabetic population.